SUSTAINING PSYCHOLOGICAL WELLBEING AMONGST MARRIED CAREER WOMEN: PSYCHOLOGICAL DISTRESS, SOCIAL SUPPORT, DOMESTIC VIOLENCE, AND FAMILY CONFLICT RESOLUTION AS INFLUENCERS - Adekanmbi, Foluso Philip; Adegoke, Steve O; Ukpere, Wilfred; Kelvin-Iloafu, Lovlyn Ekeowa (Journal of Economic Development, Environment and People, 2021)
The current paper aims to examine the influencing factors in sustaining psychological wellbeing amongst married career women in Ibadan, Nigeria. Hence, this paper plans to propose ways of increasing and sustaining psychological wellbeing amongst married career women in Ibadan, Nigeria. The paper espoused a quantitative research approach based on a survey research design. The results showed that psychological distress, social support, domestic violence, and family conflict resolution significantly jointly and independently influence the sustenance of psychological wellbeing amongst married career women in Ibadan, Nigeria. The results show that family conflict resolution is a noteworthy moderator of the negative influence of psychological distress and domestic violence in sustaining psychological wellbeing amongst married career women in Ibadan, Nigeria. Besides, the outcomes indicate that religion significantly influences psychological wellbeing amongst married career women in Ibadan, Nigeria. Therefore, developmental psychologists, organizational managers, human resources practitioners, counselors, and religious organizations should encourage ways of reducing psychological distress, by increasing social support, reducing domestic violence, and achieving consistent conflict resolution within families, as a way to sustain psychological wellbeing amongst married career women in Nigeria. Thus, this paper has recognized psychological distress, social support, domestic violence, family conflict resolution, and demographic factors (for instance, religion) as significant influencers in sustaining psychological wellbeing amongst married career women in Ibadan, Nigeria.